Collaborative Governance in Flood Management in Sumedang Regency - Rizky Ilhami; Willya Achmad (Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to examine the implementation of collaborative governance in flood control in Sumedang Regency. The research method used is a case study with data collection techniques through interviews, observation, and documentation. The research respondents consisted of representatives from local government, communities, and the private sector involved in flood management in Sawahdadap Village and Cisurupan Seda, Cimanggung District, Sumedang District. The results of the study show that collaborative governance has been implemented in flood management in Sumedang Regency through aspects of the collaborative governance dimension, which include initial conditions, institutional design, facilitative leadership, and collaborative processes. However, there are several obstacles to its implementation, such as differences in perceptions, uneven accountability and responsibility, and limited financial and human resources. Therefore, there is a need for more systematic and integrated efforts to increase collaboration between related sectors and the community in handling floods in Sumedang Regency.